Visualization and mapping of the right phrenic nerve by intracardiac echocardiography during atrial fibrillation ablation. Issue 4 (1st March 2023) - Liu, Xinmeng; Lin, Rong; Peng, Xiaodong; Wang, Xuesi; Li, Yukun; Liu, Xiaoxia; Wang, Wei; Yu, Ronghui; Bai, Rong; Ma, Changsheng; Ruan, Yanfei; Liu, Nian
Abstract: Objective: This study aimed to evaluate the feasibility of real-time visualization and mapping of the right phrenic nerve (RPN) by using intracardiac echocardiography (ICE) during atrial fibrillation (AF) ablation. Background: RPN injury is a complication associated with the ablation of AF. Multiple approaches are currently being used to prevent and detect RPN injuries. However, none of these approaches can directly visualize the RPN in real-time during the ablation procedure. Methods and results: The RPN was detected using ICE. The RPN and its adjacent structures were analysed. The relationship between the RPN's distance from the superior vena cava (SVC) and its pacing capture threshold was quantified. The safety of SVC isolation guided by the ICE-visualized RPN was evaluated. Thirty-eight people were enrolled in this study. The RPN was visualized by ICE in 92% of patients. It ran through the space between the SVC and the mediastinal pleura and had a 'straw'-like appearance upon ICE imaging. The course of the RPN was close to the SVC (minimum 1.0 ± 0.4 mm) and the right superior pulmonary vein (minimum 14.1 ± 7.3 mm). There was a positive linear correlation between the RPN's capture threshold and its distance from the SVC (Spearman's correlation coefficient = 0.728, < 0.001). SVC isolation was guided by the RPN; none of the patients developed an RPN injury. Conclusions: RPN can be visualized by ICE in most patients, thus providing a novel approach for the real-time detection of RPN during AF ablation. Graphical Abstract: Graphical Abstract A: The ICE image of the RPN. B: The anatomical relationship between RPN and SVC, RSPV, sinus node in the 3D activation map. C: There was a positive linear correlation between the RPN's capture threshold and its distance from the SVC.